2017
DOI: 10.1128/jb.00119-16
|View full text |Cite
|
Sign up to set email alerts
|

Negative Regulation of Ectoine Uptake and Catabolism in Sinorhizobium meliloti: Characterization of the EhuR Gene

Abstract: Ectoine has osmoprotective effects on Sinorhizobium meliloti that differ from its effects in other bacteria. Ectoine does not accumulate in S. meliloti cells; instead, it is degraded. The products of the ehuABCD-eutABCDE operon were previously discovered to be responsible for the uptake and catabolism of ectoine in S. meliloti. However, the mechanism by which ectoine is involved in the regulation of the ehuABCD-eutABCDE operon remains unclear. The ehuR gene, which is upstream of and oriented in the same direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(37 citation statements)
references
References 33 publications
1
35
1
Order By: Relevance
“…We, and others, have recently shown that EnuR (= EhuR) serves as a repressor for ectoine catabolism (Schulz et al ., ; Yu et al ., ). Therefore, it came somewhat as a surprise that the uehA‐lacZ reporter fusion present on the enuR + plasmid pBAS20 exhibited higher induction levels in response to ectoines in comparison with plasmid pBAS21 that lacks an intact enuR regulatory gene (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…We, and others, have recently shown that EnuR (= EhuR) serves as a repressor for ectoine catabolism (Schulz et al ., ; Yu et al ., ). Therefore, it came somewhat as a surprise that the uehA‐lacZ reporter fusion present on the enuR + plasmid pBAS20 exhibited higher induction levels in response to ectoines in comparison with plasmid pBAS21 that lacks an intact enuR regulatory gene (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…C). This is consistent with the notion that EnuR acts genetically as a repressor (Schulz et al ., ; Yu et al ., ). Induction of the reporter fusion by either ectoine or hydroxyectoine in a chromosomal enuR deletion strain was less prominent, but was not completely eliminated (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Ectoine, aspartate and PLP exhibited no effects on the binding of EhuR to DNA probes. In contrast, DABA (a degradation product in the ectoine catabolism pathway) alone can inhibit the binding of EhuR to both promoters in a concentration‐dependent manner, with a slightly stronger inhibitory effect on the binding to ehuA promoter .…”
Section: Interactions Between Mocr‐tfs and Dnamentioning
confidence: 97%
“…meliloti, a soil bacterium that can be found either free‐living or on the roots of leguminous plants, the ehuABCD‐eutABCDE operon is involved in ectoine uptake and catabolism . A mocR gene ( ehuR ; http://www.ncbi.nlm.nih.gov/protein/SMB_20426) is located upstream of this operon and oriented in the same direction . Although ehuR and ehuABCD‐eutABCDE form a polycistronic transcriptional unit, ehuABCD‐eutABCDE has its own promoter.…”
Section: Characterised Mocr‐tfs and Their Functional Characteristicsmentioning
confidence: 99%